Fiber-Reinforced Polymer Composites in the Construction of Bridges: Opportunities, Problems and Challenges - Paweł Grzegorz Kossakowski; Wiktor Wciślik (Fibers, 2022)
In this review, we discuss the basic issues related to the use of FRP (fiber-reinforced polymer) composites in bridge construction. This modern material is presented in detail in terms of the possibility of application in engineering structures. A general historical outline of the use and development of modern structural materials, such as steel and concrete, is included to introduce composites as a novel material in engineering, and the most important features and advantages of polymers as a construction material are characterized. We also compare FRP to basic structural materials, such as steel and concrete, which enables estimation of the effectiveness of using of FRP polymers as structural material in different applications. The first bridges made of FRP composites are presented and analyzed in terms of applied technological solutions. Examples of structural solutions for deck slabs, girders and other deck elements made of FRP composites are discussed. Particular attention is paid to the systems of deck slabs, especially those composed of pultruded profiles, sandwich panels and hybrid decks. The disadvantages of composites, as well as barriers and limitations in their application in engineering practice, are presented. Exemplary analyses of the costs of construction, maintenance and demolition of FRP composite bridges are presented and compared with the corresponding costs of concrete and steel bridges. The directions of development of composite bridge structures and the greatest challenges facing engineers and constructors in the coming years are discussed.